Information culture thematic in theses and dissertations of Brazilians graduate programs in Information Science - Santos, Cassia Dias; Pomim Valentim, Marta Ligia [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2019)
Presents a bibliometric analysis of national theses and dissertations about the thematic informational culture. Seeks to identify the conceptions and approaches, the postgraduate programs and the most influential authors on subject. Mapping the scientific production on information culture in the afore mentioned scope, the search process occurred through the Brazilian Digital Library of Theses and Dissertations, not being established a chronological delimitation. From the selection and analysis of the material, found a total of 16 works were obtained. From the analysis, it was possible to extract the conceptions adopted and the methodological and thematic approaches adopted by each author. The results showed that the information culture is present in a variety of studies whose are different interest. Observed that the exploratory qualitative and descriptive researches are predominant in the analyzed universe, coming from five universities. From the citation analysis, the authors Davenport and Prusak stand out among the most influential. It is also evidenced that most theses and dissertations are based on research developed by researchers from Information Science scientific field. It is considered that, although late, the informational culture in the theses and dissertations indicate a certain effort of the researchers to contribute with new theoretical and methodological constructions around this theme. However, this study reflects that in the scope of Brazilian Information Science, there are still few graduate programs incorporating this subject as an object of research, a factor that consequently impacts on low scientific productivity about this subject.
Keywords: Bibliometrics; Information Science; Information Culture